2018
DOI: 10.1111/aor.13127
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐Specific Atrial Hemodynamics of a Double Lumen Neonatal Cannula in Correct Caval Position

Abstract: Clinical success of pediatric veno‐venous (VV) extracorporeal membrane oxygenation (ECMO) is associated with the double lumen cannula cardiovascular device design as well as its anatomic orientation in the atrium. The positions of cannula ports with respect to the vena cavae and the tricuspid valve are believed to play a significant role on device hemodynamics. Despite various improvements in ECMO catheters, especially for the neonatal and congenital heart patients, it is still challenging to select a catalogu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 18 publications
4
17
0
Order By: Relevance
“…This obviously shows that a turbulent outflow is more favorable in aortic cannulas if optimal perfusion characteristics are desired. Another important issue which can be frequently faced in the literature, especially during the computational simulations is the decision on whether the outflow of aortic cannula should be treated as laminar or turbulent . Our results confirmed that even for relatively low Reynolds flows, the outflow shows strong turbulence which builds as early as 3‐4 jet diameters downstream of the exit tip.…”
Section: Discussionsupporting
confidence: 76%
“…This obviously shows that a turbulent outflow is more favorable in aortic cannulas if optimal perfusion characteristics are desired. Another important issue which can be frequently faced in the literature, especially during the computational simulations is the decision on whether the outflow of aortic cannula should be treated as laminar or turbulent . Our results confirmed that even for relatively low Reynolds flows, the outflow shows strong turbulence which builds as early as 3‐4 jet diameters downstream of the exit tip.…”
Section: Discussionsupporting
confidence: 76%
“…The 3D reconstructions of the DLC and atrium were combined in the computer as reported in our previous study. 12 Here, clinical malpositioned configurations are generated to simulate clinical scenarios and numerical algorithm was adapted to allow for site-specific determination of the hemodynamic parameters. As shown in Figure 1, a total of six cases of malposition were simulated, consisting of two rotations (antero-atrial and atrio-septal) and four translations (two retrograde movements inside the IVC, two dislodgements in the atrium).…”
Section: Methodsmentioning
confidence: 99%
“…This solver has been recently applied to neonatal aortic cannulas 19 as well as DLC by our group and validated experimentally. 12,20 The discrete system of Reynolds-averaged Navier–Stokes (RANS) equation was solved using Semi-Implicit Pressure Linked Equation (SIMPLE) solver and each simulation took around 8 hours on a Dell Precision T7600 desktop computer with dual core Xeon processors. Second-order accuracy for diffusive and convective fluxes was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Jamil Muhammad et al of Koç University, Sarıyer, Turkey, investigated the complex flow regime of a neonatal double lumen cannula in veno‐venous extracorporeal membrane oxygenation (ECMO) with the double lumen cannula positioned in a patient‐specific right atrium. A pulsatile computational fluid dynamics (CFD) solver was used to perform the detailed flow, oxygenated blood transport, and site‐specific blood damage analysis using an integrated cannula and right atrium model.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%